Lithium metal negative electrode material and preparation method and application thereof

The preparation of lithium metal anode materials by dual-temperature zone furnace method and vapor deposition-alloying process solves the problem of lithium dendrite formation, achieves high cycle reversibility and structural stability of materials, simplifies the preparation process and reduces environmental pollution.

CN120413654BActive Publication Date: 2025-11-18GANZHOU NUOWEI NEW ENERGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510873081.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-27
Publication Date
2025-11-18
Estimated Expiration
2045-06-27

AI Technical Summary

Technical Problem

Lithium metal anodes are prone to forming lithium dendrites during charging and discharging, which can lead to battery short circuits and safety hazards. In addition, traditional preparation processes are complex and solvent volatilization pollutes the environment.

Method used

Lithium metal anode materials are prepared using a dual-temperature zone furnace method. This method involves heating a low-boiling-point metal M in a high-temperature zone and depositing it onto the surface of a lithium sheet in a low-temperature zone to form a lithium layer and a surface composite layer LiM. Combined with a vapor deposition-alloying process, a tightly bonded lithium layer and LiM layer are formed, avoiding the use of binders.

Benefits of technology

It improves the cycle reversibility and structural stability of lithium metal anode materials, reduces the possibility of lithium dendrite formation, enhances battery safety and electrochemical performance, simplifies the preparation process, and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120413654B_ABST
    Figure CN120413654B_ABST
Patent Text Reader

Abstract

The application belongs to the field of lithium ion battery materials, and discloses a lithium metal negative electrode material and a preparation method and application thereof, wherein the lithium metal negative electrode material comprises a lithium layer and a surface composite layer; the lithium layer is lithium monomer; and the surface composite layer is LiM, and M is any one or two or more of Zn, Bi and Sn. The lithium metal negative electrode material has a double-layer structure, the main body layer is lithium monomer, and the surface composite layer is LiM, so that the possibility of forming lithium dendrites of the lithium metal negative electrode material under high working voltage can be reduced, and the negative electrode material exhibits excellent cycle reversibility and structural stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion battery materials, and relates to lithium-ion battery anode materials, specifically to a lithium metal anode material and its preparation method and application. Background Technology

[0002] Lithium metal anodes offer advantages such as high specific capacity and high operating voltage, contributing to improved energy density and charging speed in lithium batteries. The theoretical specific capacity of lithium metal anodes reaches 3860 mAh / g, more than 10 times that of traditional graphite anodes (372 mAh / g). In the same volume, lithium metal anodes can store more charge, thus extending battery life. The high operating voltage of lithium metal anodes reduces battery internal resistance, thereby increasing charging speed and significantly shortening charging time for devices such as electric vehicles. However, during charge-discharge cycles, lithium metal anodes are prone to lithium dendrite formation, which can potentially puncture the separator, leading to battery short circuits and safety hazards. Summary of the Invention

[0003] In view of the defects and deficiencies of the existing technology, the present invention provides, firstly, a method for preparing a lithium metal anode material; secondly, a lithium metal anode material; and thirdly, a battery.

[0004] In a first aspect, the present invention provides a lithium metal anode material, comprising a lithium layer and a surface composite layer, wherein the surface composite layer is located on any side of the lithium layer; the lithium layer is elemental lithium, and the surface composite layer is LiM, wherein M is any one or more of Zn, Bi, and Sn.

[0005] Secondly, the present invention provides a method for preparing a lithium metal anode material, comprising the following steps:

[0006] Step 1: Place the low-boiling-point metal M in the high-temperature zone of the dual-temperature zone furnace and the lithium metal sheet in the low-temperature zone of the dual-temperature zone furnace. Heat in an inert atmosphere and continuously circulate gas into the dual-temperature zone furnace. The gas flows from the high-temperature zone to the low-temperature zone.

[0007] Step 2: Cool the product obtained in Step 1 to obtain the lithium metal anode material;

[0008] The low-boiling-point metal M is any one or more of nano zinc powder, nano bismuth powder, and nano tin powder.

[0009] Preferably, the D50 of the low-boiling-point metal M is 20~100nm.

[0010] Preferably, the mass ratio of low-boiling-point metal M to lithium sheet is 0.3~0.8:1.

[0011] Preferably, the thickness of the lithium metal sheet is 100~300μm.

[0012] Preferably, the high-temperature zone roasting temperature is 600~900℃; the low-temperature zone roasting temperature is 160~200℃; and the roasting time is 1~3h.

[0013] Preferably, the gas providing the inert atmosphere is either nitrogen or argon.

[0014] Preferably, in step 2, the product obtained in step 1 is cooled to 30-50°C within 0.5-2 hours.

[0015] Thirdly, the present invention provides a battery comprising the above-described lithium metal anode material or the lithium metal anode material prepared by the above-described preparation method.

[0016] Compared with the prior art, the present invention has the following significant advantages:

[0017] (1) The lithium metal anode material provided by the present invention has a double-layer structure, with the main layer being elemental lithium and the surface composite layer being LiM, which can reduce the possibility of lithium dendrites forming under high working voltage of lithium metal anode material, thereby enabling the anode material to exhibit excellent cycle reversibility and structural stability.

[0018] (2) The preparation process provided by the present invention alloys the low-boiling-point metal M and the lithium on the surface of the metal lithium sheet into LiM without the need for a binder, making the bond between the lithium layer and the LiM layer tighter and reducing the possibility of volume expansion of the negative electrode material during battery operation.

[0019] (3) The preparation method provided by the present invention combines vapor deposition-alloying and rapid cooling processes to obtain low crystallinity LiM@Li lithium metal anode material, which can effectively suppress lithium dendrites, reduce the risk of battery separator being punctured, and improve the safety and electrochemical performance of the battery. Attached Figure Description

[0020] Figure 1 This is a schematic diagram obtained by XPS testing of the alloy layer of the lithium metal anode material prepared in Example 1.

[0021] Figure 2 This is a schematic diagram obtained from XPS testing of zinc sheets;

[0022] Figure 3 A schematic diagram obtained by XPS testing of the lithium layer of the lithium metal anode material prepared in Example 1.

[0023] Figure 4 The cycling performance test curves are for batteries assembled from lithium metal anode materials and lithium metal sheets prepared in Examples 1-3 and Comparative Examples 1-3. Detailed Implementation

[0024] The present invention provides the following specific technical solutions.

[0025] In a first aspect, the present invention provides a lithium metal anode material, comprising a lithium layer and a surface composite layer, wherein the surface composite layer is located on any side of the lithium layer; the lithium layer is elemental lithium, and the surface composite layer is LiM, wherein M is any one or more of Zn, Bi, and Sn.

[0026] Through research, the inventors discovered that lithium metal anode materials possess a bilayer structure, with the main layer being elemental lithium and the surface composite layer being LiM. Firstly, the ionic conductivity and mechanical strength of the LiM alloy are higher than those of pure lithium. As a surface composite layer, the LiM alloy provides mechanical support, reducing the possibility of lithium layer collapse or acting as a physical barrier to inhibit lithium dendrite puncture. Secondly, the alloy layer exhibits lower reactivity with the electrolyte than pure lithium, forming a more stable SEI film and reducing continuous side reactions between lithium and the electrolyte (such as the "shuttle effect" and the formation of "dead lithium"), thus improving cycle life. Thirdly, the lithium layer undergoes significant volume changes during charging and discharging, while the LiM alloy experiences smaller volume changes. The bilayer structure, through an elastic modulus gradient design (soft lithium layer → hard alloy layer), alleviates stress concentration at the interface, avoiding cracking or peeling caused by volume changes in traditional electrodes. The gradient interface can also suppress volume expansion to a certain extent. Under battery cycling or external force, the dual-layer structure combines the rigid framework of the alloy layer with the ductility of the lithium layer to achieve a balance between rigidity and flexibility, reducing electrode damage caused by mechanical stress and improving battery safety. Fourthly, LiM alloys typically have a higher lithium-ion diffusion coefficient, which can reduce interface impedance and improve fast charging performance.

[0027] In summary, the lithium metal anode material provided by this invention exhibits excellent cycle reversibility and structural stability when applied in batteries.

[0028] Secondly, the present invention provides a method for preparing a lithium metal anode material, comprising the following steps:

[0029] Step 1: Place the low-boiling-point metal M in the high-temperature zone of the dual-temperature zone furnace and the lithium metal sheet in the low-temperature zone of the dual-temperature zone furnace. Heat in an inert atmosphere and continuously circulate gas into the dual-temperature zone furnace. The gas flows from the high-temperature zone to the low-temperature zone.

[0030] Step 2: Cool the product obtained in Step 1 to obtain the lithium metal anode material;

[0031] The low-boiling-point metal M is any one or more of nano zinc powder, nano bismuth powder, and nano tin powder.

[0032] The inventors discovered through research that the traditional process for preparing composite electrodes typically involves steps such as mixing binders and composite materials, coating slurry, and drying solvents. This process is complex, and the solvents (such as NMP) are volatile and pollute the environment, requiring additional recycling and treatment.

[0033] The process provided by this invention utilizes a one-step vapor deposition-alloying method. A low-boiling-point metal M is heated and volatilized in a high-temperature region, depositing onto the surface of a lithium metal sheet in a low-temperature region. Furthermore, the low-boiling-point metal M and the lithium on the lithium metal sheet surface are alloyed to form LiM. This method achieves an integrated negative electrode material with a lithium layer and surface composite layer without the need for a binder. The preparation process provided by this invention offers the following advantages over existing binder-based negative electrode materials:

[0034] First, the bonding between the lithium layer and the surface composite layer (LiM layer) is tighter. The alloy layer and the lithium layer are directly bonded by metal bonds, resulting in extremely low resistance to electron transport at the interface. Compared with the multi-stage transport paths in traditional binder electrodes, this can significantly reduce the internal resistance of the electrode and improve the power density.

[0035] Second, binders usually fix active materials through the physical adsorption or mechanical entanglement of polymer materials. However, during charging and discharging, the volume change (expansion / contraction) of lithium metal can easily cause the binder to peel off from the lithium layer, leading to interface failure. Low-boiling-point metal M and lithium form LiM alloys (such as Li-Zn, Li-Sn, etc.) through atomic diffusion. Metal bonding or solid solution structures are formed at the interface, and the bonding strength is much higher than the physical adhesion of the binder. It can withstand greater volume changes without falling off.

[0036] Third, in binder systems, tiny voids often arise due to solvent evaporation or polymer chain contraction, leading to poor interfacial contact and increased resistance. However, the lithium metal anode material prepared by the process provided in this invention achieves atomic-level tight bonding through alloying, with no pores at the interface, thereby achieving low-resistance conduction and improving electron transport efficiency.

[0037] Fourth, the process is short, requires no solvents, conforms to the concept of green manufacturing, and reduces equipment investment and energy costs.

[0038] Fifth, the polymer materials in the binder are mostly organic flammable materials, which may exacerbate thermal runaway under battery overcharging or high temperature; while the electrode components provided by this invention are all metals or alloys, without organic polymers, and have higher thermal stability, which can reduce the risk of battery fire or explosion.

[0039] Preferably, the diameter of the low-boiling-point metal M is 20~100nm.

[0040] Through research, the inventors discovered that by controlling the size of the low-boiling-point metal M, the reaction between the low-boiling-point metal M and the lithium metal sheet can be made more complete, improving the composite effect and thus enhancing the quality of the resulting lithium metal anode material.

[0041] Preferably, the mass ratio of the low-boiling-point metal M in the high-temperature furnace to the lithium sheet in the low-temperature furnace is 0.3~0.8:1.

[0042] Preferably, the thickness of the lithium metal sheet is 100~300μm.

[0043] Preferably, the gas providing the inert atmosphere is either nitrogen or argon.

[0044] Preferably, the high-temperature zone roasting temperature is 600~900℃, the low-temperature zone roasting temperature is 160~200℃, and the roasting time is 1~3h.

[0045] Through research, the inventors discovered that within the aforementioned preferred range, low-boiling-point metal M and lithium metal can undergo a sufficient alloying reaction to form an alloy phase with specific structure and properties. This enables the lithium metal anode material to form a bilayer structure of lithium layer and LiM layer, increasing the diffusion channels of lithium ions, improving the ionic conductivity of the material, and thus improving the charge and discharge performance of the battery. By adjusting the reaction time, the composition and structure of the alloy phase can be made more uniform, thereby improving the performance of the lithium metal anode material.

[0046] Preferably, in step 2, the product obtained in step 1 is cooled to 30-50°C within 0.5-2 hours.

[0047] Thirdly, the present invention provides a battery comprising the above-described lithium metal anode material or the lithium metal anode material prepared by the above-described preparation method.

[0048] To make the technical problems, technical solutions and technical advantages of the present invention clearer, a detailed description will be given below with reference to specific examples. However, the scope of protection of the present invention is not limited to the following specific embodiments.

[0049] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.

[0050] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.

[0051] Example 1:

[0052] A method for preparing a lithium metal anode material, using a dual-temperature zone furnace and reacting under a nitrogen atmosphere, includes the following steps:

[0053] Step 1: Place 1.5g of nano zinc powder (80nm) in the high-temperature zone of the gas inlet, and place 3g of lithium sheet with a thickness of 200μm in the low-temperature zone of the gas outlet. Continuously introduce nitrogen into the dual-temperature zone furnace, and then raise the temperature. The high-temperature zone calcination temperature is 750℃, and the low-temperature zone calcination temperature is 180℃. Hold the reaction for 2 hours.

[0054] Step 2: Cool the product obtained in Step 1 to room temperature within 1 hour to obtain the lithium metal anode material.

[0055] Comparative Example 1:

[0056] A method for preparing a lithium metal anode material, using a conventional tube furnace and reacting under a nitrogen atmosphere, includes the following steps:

[0057] Step 1: 1.5g of low-boiling-point metallic nano zinc powder (80nm) is evenly spread on the surface of 3g of lithium sheet with a thickness of 200μm, and then the temperature is raised to 180℃ and kept at that temperature for 2h.

[0058] Step 2, step 2, cool the product obtained in step 1 to room temperature within 1 hour to obtain the lithium metal anode material.

[0059] The lithium metal anode material prepared in Comparative Example 1 has a granular surface. The nano zinc powder adheres to the lithium sheet in some areas where it contacts the lithium sheet. The inventors speculate that this may be because the reaction temperature is too low, causing the lithium metal to melt and adhere to fix the nano zinc powder, which may result in alloying in some areas where the nano zinc powder and the lithium sheet are in contact.

[0060] Comparative Example 2:

[0061] A method for preparing a lithium metal anode material, using a conventional tube furnace and reacting under a nitrogen atmosphere, includes the following steps:

[0062] Step 1: 1.5g of low-boiling-point metallic nano zinc powder (80nm) is evenly spread on the surface of 3g of lithium sheet with a thickness of 200μm, and then the temperature is raised to 750℃ and kept at that temperature for 2h.

[0063] Step 2, step 2, cool the product obtained in step 1 to room temperature within 1 hour to obtain the lithium metal anode material.

[0064] During the reaction, lithium foil and zinc powder are completely liquefied and alloyed to form a homogeneous LiZn alloy composite lithium metal anode material.

[0065] Comparative Example 3:

[0066] A method for preparing a lithium metal anode material includes the following steps:

[0067] Step 1: Place 5g of nano zinc powder (80nm) and 5g of nano lithium powder (50nm) under a nitrogen atmosphere and calcine at 750℃ for 2h. Then, take out the product, crush it, and obtain LiZn alloy nanoparticles with D50 of 80nm.

[0068] Step 2: Disperse 1.5g of the LiZn alloy nanoparticles prepared in Step 1 and 1.25g of polyvinyl alcohol in 40mL of N-methylpyrrolidone and grind them to form a uniformly distributed slurry.

[0069] Step 3: Use a coating machine to evenly coat the slurry obtained in step 2 onto one side of a 3g lithium sheet with a thickness of 200μm. After drying, the lithium metal anode material can be obtained.

[0070] Example 2:

[0071] A method for preparing a lithium metal anode material, using a dual-temperature zone furnace and reacting under a nitrogen atmosphere, includes the following steps:

[0072] Step 1: Place 0.9g of nano-bismuth powder (20nm) in the high-temperature zone of the gas inlet, and place 3g of lithium sheet with a thickness of 100μm in the low-temperature zone of the gas outlet. Continuously introduce nitrogen into the dual-temperature zone furnace, and then raise the temperature. The high-temperature zone calcination temperature is 600℃, and the low-temperature zone calcination temperature is 160℃. Hold the reaction at this temperature for 3 hours.

[0073] Step 2: Cool the product obtained in Step 1 to room temperature within 0.5 hours to obtain the lithium metal anode material.

[0074] Example 3:

[0075] A method for preparing a lithium metal anode material, using a dual-temperature zone furnace and reacting under a nitrogen atmosphere, includes the following steps:

[0076] Step 1: Place 2.4g of nano-tin powder (100nm) in the high-temperature zone of the gas inlet, and place 3g of lithium sheet with a thickness of 300μm in the low-temperature zone of the gas outlet. Continuously introduce nitrogen into the dual-temperature zone furnace, and then raise the temperature. The high-temperature zone calcination temperature is 900℃, and the low-temperature zone calcination temperature is 200℃. Hold the reaction at this temperature for 3 hours.

[0077] Step 2: Cool the product obtained in Step 1 to room temperature within 2 hours to obtain the lithium metal anode material.

[0078] XPS tests were performed on the lithium metal anode material and zinc sheet prepared in Example 1. Figure 1 This is a schematic diagram obtained from XPS testing of the alloy layer of the lithium metal anode material. Figure 2 This is a schematic diagram obtained from an XPS test on a zinc sheet. Figure 3This is a schematic diagram obtained from XPS testing of the lithium layer of a lithium metal anode material.

[0079] from Figure 1 The presence of the 2p characteristic peak of Zn indicates that zinc exists in the surface layer of the lithium anode. The binding energy corresponding to the 2p² / ³ peak of Zn is 1022.1 eV. Figure 2 It can be seen that the binding energy of the characteristic peak of pure zinc is 1020.5 eV, compared to Figure 1 and Figure 2 It can be seen that the 2p2 / 3 peak of Zn has shifted positively, indicating that the electron cloud density of Zn atoms has decreased and some Zn atoms have changed from 0 oxidation state to partially positive oxidation state, confirming the formation of Zn-Li chemical bond.

[0080] Depend on Figure 3 The results show that there is no 2p characteristic peak of Zn in the lithium layer, which proves that the lithium layer is a pure lithium metal phase and there is no LiZn alloy phase present.

[0081] In summary, this invention demonstrates that the modified lithium metal anode prepared by this invention is a composite structure of a lithium layer and a LiZn alloy layer.

[0082] Figure 4 The cycling performance test curves are for batteries assembled from lithium metal anode materials and lithium metal sheets prepared in Examples 1-3 and Comparative Examples 1-3.

[0083] The lithium metal anode materials prepared in Examples 1-3 and Comparative Examples 1-3 were stamped with a lithium metal sheet with a thickness of 0.1 mm into a diameter of 16 mm to serve as the anode. Commercial ternary materials were mixed with conductive agent acetylene black (AB) and binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) was used as a solvent. The mixture was stirred at 800 r / min for 2 h to obtain a slurry. The slurry was coated onto the current collector aluminum foil using an automatic coating machine, laid flat on tempered glass, and dried in a vacuum drying oven at 85°C for 4 hours. After being punched into positive electrode sheets with a diameter of 12 mm, the sheets were dried in a vacuum drying oven at 105°C for 4 hours. The sheets were then placed in a glove box filled with argon atmosphere with a water and oxygen content of less than 0.1 ppm to reduce the moisture adsorbed by the sheets during the transfer process. Finally, the sheets were assembled into CR2032 coin cells in the glove box, with a porous polyethylene membrane of model Celgard2300 with a diameter of 18 mm as the separator.

[0084] After the battery assembly was completed and aged for 12 hours, a 1C rate charge-discharge test was conducted within a voltage range of 3~4.4V. The test results are as follows. Figure 4 As shown.

[0085] The lithium metal anode material prepared in Example 1 has a lithium metal main body layer and a LiZn alloy surface composite layer; the lithium metal anode material prepared in Comparative Example 1 has a lithium metal main body layer and a Zn layer surface layer. Figure 1 It can be seen that the battery assembled from the lithium metal anode material prepared in Example 1 has better cycle performance under high voltage. The inventors speculate that this may be because the composite layer can reduce the possibility of lithium dendrite formation while ensuring the high working voltage of the lithium metal anode material, thereby making the anode material exhibit excellent cycle reversibility and structural stability.

[0086] The lithium metal anode material prepared in Comparative Example 2 is a homogeneous LiZn alloy. The inventors pointed out that a single LiZn alloy has poor energy storage capacity, and the single alloy structure affects the diffusion of lithium ions, reduces the lithium diffusion capacity, and ultimately affects the electrochemical performance of the battery.

[0087] The lithium metal anode material prepared in Comparative Example 3 is also a composite structure of lithium layer and LiZn layer. However, LiZn is adhered to the lithium layer surface by a binder. Compared with the battery assembled from the lithium metal anode material prepared in Comparative Example 3, the battery assembled from the lithium metal anode material prepared in Example 1 has better cycle performance. The inventors speculate that this may be because: in Example 1, the nano zinc powder is alloyed with lithium sheet, and the resulting lithium layer and LiM layer are integrated. The structure of the electrode is more compact and stable. During cycling, it can better withstand the insertion and extraction of lithium ions and reduce structural damage caused by factors such as volume changes, thus exhibiting better cycle stability.

[0088] Compared to other samples, the unmodified lithium foil had the worst performance. The inventors speculate that this may be because lithium dendrites and uneven deposition layers form on the lithium anode after long cycling, which makes the electrochemical performance of the battery unstable during cycling and causes the capacity to decay quickly.

[0089] The above-described embodiments are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the technical scope of the present invention, based on the technical solution and concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing a lithium metal negative electrode material, characterized by, Includes the following steps: Step 1: Place the low-boiling-point metal M in the high-temperature zone of the dual-temperature zone furnace and the lithium metal sheet in the low-temperature zone of the dual-temperature zone furnace. Heat in an inert atmosphere and continuously circulate gas into the dual-temperature zone furnace. The gas flows from the high-temperature zone to the low-temperature zone. Step 2: Cool the product obtained in Step 1 to obtain the lithium metal anode material; Wherein, the low-boiling-point metal M is any one or more of nano zinc powder, nano bismuth powder and nano tin powder; The high-temperature zone roasting temperature is 600~900℃; the low-temperature zone roasting temperature is 160~200℃. The lithium metal anode material includes a lithium layer and a surface composite layer, wherein the surface composite layer is located on any side of the lithium layer; the lithium layer is elemental lithium, and the surface composite layer is LiM, wherein M is any one or more of Zn, Bi, and Sn.

2. The method for preparing the lithium metal anode material as described in claim 1, characterized in that, The D50 of the low-boiling-point metal M is 20~100nm.

3. The method for preparing the lithium metal anode material as described in claim 1, characterized in that, The mass ratio of low-boiling-point metal M to lithium foil is 0.3~0.8:

1.

4. The method for preparing the lithium metal anode material as described in claim 1 or 3, characterized in that, The thickness of the lithium metal sheet is 100~300μm.

5. The method for preparing the lithium metal anode material as described in claim 1, characterized in that, The gas providing the inert atmosphere is either nitrogen or argon, or both.

6. The method for preparing the lithium metal anode material as described in claim 1, characterized in that, In step 2, the product obtained in step 1 is cooled to 30-50°C within 0.5-2 hours.

7. The method for preparing the lithium metal anode material as described in claim 1, characterized in that, The roasting time is 1 to 3 hours.

Citation Information

Patent Citations

  • Laminated lithium metal battery negative electrode material, preparation method thereof and lithium metal secondary battery

    CN112750982A

  • Surface-alloyed metal lithium foil and preparation method thereof, metal lithium negative electrode and lithium battery

    CN113594426A

  • Inert lithium powder, preparation method thereof, lithium ion battery electrode material containing inert lithium powder and lithium ion battery

    CN116646486A

  • Negative electrode and li secondary battery

    JP1995296812A